Violencia y conflictos (Padres y Maestros / Journal of Parents and Teachers, 2023)
The article presents some websites that discuss the conflicts that occur in schools. It’s mainly orientated for families and teacher to know the causes and how they can solve the problems. It includes a section with English and Spanish websites.
Keywords: conflicto; violencia; web